Snow avalanches, land use changes, and atmospheric warming in landscape dynamics of the Atlantic mid-mountains (Cantabrian Range, NW Spain). (June 2019) - Beato Bergua, Salvador; Poblete Piedrabuena, Miguel Ángel; Marino Alfonso, José Luis
Abstract: The repercussions of snow avalanches, land use changes, and atmospheric warming on landscape dynamics are very important in Atlantic mid-mountains but have received little research attention in comparison to other zones and types of ecological processes. Snow avalanche disturbance have been studied without being to other aspects such as the abandonment of traditional agrosilvopastoral activities and the amplification of snowfall due to climate change. The main objective is to analyse interactions between snow avalanches, land use change, climatic warming, and their effects on the mid-mountain landscape in the Asturian Central Massif (Cantabrian Range, NW Spain). The applied methodology has involved field work, photointerpretation, geomorphological and phytosociological transects, as well as the analysis of climatic variables. This interdisciplinary combination has been completed with statistical, historical and GIS analysis. The depopulation and abandonment of traditional productive activities in the Atlantic mid-mountain explains the reduction of grasslands and the spontaneous reforestation of the forest area. However, the effectiveness and intensity of snow avalanches currently prevent the growth and recovery of the forests. Specifically, they affect 173.15 km 2 area of the Asturian Massif. In the Sierra del Aramo 370 ha are deforested by snow avalanches. There is a change in snowiness and in its behaviour (copious snowfall concentrated into storms lasting several days). The mid-mountain is affected by snow avalanches even in mid-latitudes and despite atmospheric warming. The disturbing effects of snow avalanches on the landscape dynamics prevent reforestation favoured by depopulation and changes in land use. Highlights: Climate change favours concentrated snowstorms and the triggering of snow avalanches. Snow avalanches are very frequent and intense even in the mid-latitudes mid-mountains. The depopulation and land use changes explain the spontaneous reforestation. Reforestation does not always prevent the triggering of snow avalanches. Snow avalanches role in the landscape dynamics in the mid-mountains is outstanding.